"Syndemic moral distress": sexual health provider practices in the context of co-occurring, socially produced sexual and mental health epidemics - Travis Salway; Stéphanie Black; Angel Kennedy; Sarah Watt; Olivier Ferlatte; Mark Gaspar; Rod Knight; Mark Gilbert (BMC, 2022)
Abstract Background 'Syndemic' refers to socially produced, intertwined, and co-occurring epidemics. Syndemic theory is increasingly used to understand the population-level relationships between sexual health (including HIV) and mental health (including problematic substance use) epidemics. Syndemic-informed clinical interventions are rare. Methods We therefore asked 22 sexual health practitioners from six sexual health clinics in British Columbia, Canada to define the word 'syndemic' and then asked how the theory related to their clinical practice. Results Responses to syndemic theory ranged widely, with some practitioners providing nuanced and clinically informed definitions, others expressing a vague familiarity with the term, and others still having no prior knowledge of it. Where practitioners acknowledged the relevance of syndemic theory to their practice, they articulated specific ways in which syndemics create moral distress, that is, feeling that the most ethical course of action is different from what they are mandated to do. While some practitioners routinely used open-ended questions to understand the social and economic contexts of patients' sexual health needs, they described an uneasiness at potentially having surfaced concerns that could not be addressed in the sexual health clinic. Many observed persistent social, mental health, and substance use-related needs among their patients, but were unable to find feasible solutions to these issues. Conclusions We therefore propose that interventions are needed to support sexual health practitioners in addressing psychosocial health needs that extend beyond their scope of practice, thereby reducing 'syndemic moral distress'.